2022
DOI: 10.1097/bot.0000000000002256
|View full text |Cite
|
Sign up to set email alerts
|

Reamer Irrigator Aspirator Versus Iliac Crest Bone Grafting and Proximal Tibial Curettage: Is There a Difference in Blood Loss and Transfusion Rates?

Abstract: Objectives: To compare blood loss and transfusion rates among reamer irrigator aspirator (RIA), iliac crest bone graft (ICBG), and proximal tibial curettage (PTC) for autograft harvest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Thirteen studies [ 18 , 42 , 43 , 45 , 47 , 48 , 50 , 55 60 ] reported blood loss in a total number of 336 performed procedures with the RIA system. Of these 13 studies, five studies [ 47 , 48 , 50 , 56 , 58 ] reported the volume of blood lost, which resulted in a mean of 803.29 ml per case. Furthermore, five out of the 13 studies reported a drop in hemoglobin, resulting in a mean of 3.74 g/dl.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen studies [ 18 , 42 , 43 , 45 , 47 , 48 , 50 , 55 60 ] reported blood loss in a total number of 336 performed procedures with the RIA system. Of these 13 studies, five studies [ 47 , 48 , 50 , 56 , 58 ] reported the volume of blood lost, which resulted in a mean of 803.29 ml per case. Furthermore, five out of the 13 studies reported a drop in hemoglobin, resulting in a mean of 3.74 g/dl.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, five out of the 13 studies reported a drop in hemoglobin, resulting in a mean of 3.74 g/dl. In total, 60 out of 583 patients (9.72%) included in the studies [ 18 , 42 , 43 , 45 , 47 , 48 , 57 , 59 , 60 ] required blood transfusion. The findings on blood loss are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of an atrophic or hypotrophic pseudarthrosis, vitalizing of the bony edges and implantation of a cancellous bone graft, e.g., of the iliac crest, the proximal tibia or from the calcaneus, is generally considered as gold standard. Alternatively, autologous intramedullary bone grafts can also be harvested from the femoral shaft using the Reamer-irrigator aspirator device (RIA) [ 3 , 4 , 5 ]. However, supply is often limited, and these treatment options have demonstrated varied success rates.…”
Section: Introductionmentioning
confidence: 99%